2000
DOI: 10.1016/s0142-9612(00)00005-3
|View full text |Cite
|
Sign up to set email alerts
|

A new peptide-based urethane polymer: synthesis, biodegradation, and potential to support cell growth in vitro

Abstract: A novel non-toxic biodegradable lysine-di-isocyanate (LDI)-based urethane polymer was developed for use in tissue engineering applications. This matrix was synthesized with highly purified LDI made from the lysine diethylester. The ethyl ester of LDI was polymerized with glycerol to form a prepolymer. LDI-glycerol prepolymer when reacted with water foamed with the liberation of CO 2 to provide a pliable spongy urethane polymer. The LDI-glycerol matrix degraded in aqueous solutions at 100, 37, 22, and 4°C at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 22 publications
3
137
0
1
Order By: Relevance
“…Polyurethane scaffolds synthesized from aliphatic and lysine-derived polyisocyanates have been reported to support cell attachment and proliferation in vitro, as well as ingrowth of new tissue and degradation to non-cytotoxic decomposition products in vivo (23,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane scaffolds synthesized from aliphatic and lysine-derived polyisocyanates have been reported to support cell attachment and proliferation in vitro, as well as ingrowth of new tissue and degradation to non-cytotoxic decomposition products in vivo (23,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of this ester group yields a carboxylic acid group in the polymer, which has been suggested to catalyze further degradation (47). For lysine-derived polyisocyanates, hydrolysis of urethane linkages to lysine has been reported, while others have reported that urethane and urea linkages are only enzymatically degraded (24,39,48). Higher soft segment content may also explain the faster degradation of the LTI materials, due to the higher %NCO (lower equivalent weight) of LTI relative to that of HDIt.…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made in the development of biodegradable PU or urethanebased polymers using less toxic diisocyanates [26]. These polymers have been explored for vascular and other tissue engineering applications [27][28][29].…”
Section: Biomimetic Mechanical Propertiesmentioning
confidence: 99%
“…FTIR spectroscopy showed an increase in hydrogen bonding as the hard segment length increased [114]. Some authors have reported that aliphatic BDI and LDI can degrade in the body to the diamine putrescine and amino acid lysine, respectively, which play an important role in cell growth and differentiation [115,116]. Guan et al [74] reported the synthesis of biodegradable PU and PUU copolymers based on PCL, BDI and a putrescine chain extender.…”
Section: Hard Segmentsmentioning
confidence: 99%